Aeroallergens in allergic rhinitis: a rural Indian survey - Joshi, Shreyas S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Allergic rhinitis is a global health problem and its incidence is increasing day by day. However, the identification of causative allergen cannot be confirmed on the basis of symptoms or history alone. Hence, skin prick test (SPT) remains the most useful test for detecting specific allergic triggers associated with allergic rhinitis and guide proper immunotherapy. The objective of the study was to study the prevalence of common aeroallergens in allergic rhinitis patients using SPT in our area. Methods: This prospective study was conducted on 150 patients with allergic rhinitis attending outpatient department of ENT. SPT was performed with 70 common aeroallergens on 150 patients more than 15 years of age with symptoms suggestive of allergic rhinitis. Results: One thirty three patients (88.6%) tested positive for at least one or more aeroallergen. Age distribution ranged from 16 years to 56 years. Out of 150 patients, 15% had episodic symptoms, 34% of patients had seasonal allergic symptoms, while 51% of patients had perennial allergic symptoms. The most common aeroallergen group implicated in SPT positivity was dust mites (42%) followed by dust (22%), grass (13%), trees (9%), insects (6%), fungi (5%) and others (3%). Conclusions: This study indicates a high prevalence of sensitivity to aeroallergens in the rural India. Skin prick test is the gold standard investigation of choice for definitive diagnosis of causative allergen in allergic rhinitis and its further treatment with immunotherapy.